Absence of a relationship between joint space narrowing and osteophyte formation in early knee osteoarthritis among Japanese community-dwelling elderly individuals: A cross-sectional study. Issue 4 (4th July 2017) - Komatsu, Daigo; Hasegawa, Yukiharu; Kojima, Toshihisa; Seki, Taisuke; Higuchi, Yoshitoshi; Ishiguro, Naoki
Abstract: Objectives : Joint space narrowing and osteophyte formation, radiographic features of knee osteoarthritis (OA), are not necessarily synchronous processes. We evaluated the relationship between medial minimum joint space width (mJSW) and osteophyte formation. Methods : We conducted a retrospective study of 1050 individuals (424 males; 626 females; mean age 64.9 years) who underwent knee radiography as part of a health screening program, between 2011 and 2013. mJSW and tibial osteophyte area (OF) were quantified using automated software. The mJSW range was subdivided into tertiles, and OF, mJSW, and quality of life (QOL) were compared among them. Correlation between OF and mJSW was evaluated. Results : In females, OF was largest and correlated with mJSW only in the lowest tertile group. Patients in the lowest mJSW tertile group had a lower QOL and higher pain than those in the other two groups. Based on our generalized additive models and a receiver operating characteristic curve analysis, an mJSW cutoff point of 3.5 mm was apparent in females, with no significant cutoff identified in males. Conclusions : OF correlates with mJSW below a cutoff value of about 3.5 mm in females. OA symptoms, namely physical function impairment and pain, increases significantly as mJSW decreases below the cutoff.